Meningkatkan Motivasi Belajar Bahasa Arab pada Siswa Sekolah Menengah Atas Melalui Pelatihan Goal Setting - Muhammad Erwan Syah; Hepi Wahyuningsih; Ratna Syifaâ€™a Rachmahana (JIP (Jurnal Intervensi Psikologi), 2016)
This study aims to determine the effect of goal setting training on students' motivation to learn Arabic. Participants were 26 students of class XI of SMA "X" Yogyakarta. They were grouping into 13 students as the experimental group and 13 students as a control group with pre-post control group design. Data were collected with Arabic learning motivation scale, interviews and observations. Result showed that both pretest-posttest (Z = -4359, P = 0.000, P <0.05) and pretest-follow up score on motivation to learn Arabic improve after treatment (Z = -2500, P = 0.012, P <0.05). Therefore goal setting training could enhance Arabic learning motivation.Â Keywords: Goal Setting Training, Arabic Learning Motivation, High School Student